Pengaruh metode pembelajaran Discovery Learning terhadap hasil belajar Mahasiswa - Lina Humairoh (STIKes Karsa Husada Garut, 2018)
This research background by students lower average are in askeb IV subjects when compared with the are average value of other subjects is 66 for the class of dahlias and 69 classes for pomegrante. Therefore, to foster student interest in this subject required a learning method of Discovery Leraning. The purpose of this study was to determine the comparative of the Discovery Learning methods implementation effect by lecture and questioning method. The study design used was nonequevalent contol group design. The samples are cahpter IV students DIII Midwifery Program Study STIKes Karsa Hudasa Garut Class A and B as many as 101 people that obtained by total sampling. Data collection is conducted by providing objective question to the students. Data analyzed by two stages that is univariate to see the frequency disrtibution and bevariate to see how great the influences. The result obtained that there is an increase in student learning results by using the Discovery Learning than the lecture questioning method. Improvements of 21.34 % Based on the p value = 0.031, with α = 0.05 then the p value < α. These result can be concluded that Ho is rejected which means that there are material differences in diseases and infections that accompany pergnancy and childbirth by discovry learning method is better than lecture questioning method. Can be concluded that the Discovery Learning method is a better method used to improve student learning result so the entire teaching staff are suggested to used to improve student learning method in the learning process by further improving the learning result in order to achieve the learning objectives.